Measuring economic freedom: an alternative functional specification and subsequent ranking. Issue 14 (21st March 2020) - Balliew, Sean; Mathews, Timothy; Hall, Joshua C.
ABSTRACT: The widely cited Economic Freedom of the World index is an aggregate measure of economic freedom calculated by using a simple arithmetic mean of scores over five sub-dimensions: (1) size of government, (2) legal structure and security of property rights, (3) access to sound money, (4) freedom to trade internationally and (5) regulation of credit, labour and business. The use of a simple arithmetic mean implicitly assumes that the different sub-dimensions are 'perfect substitutes'. To explore the implications of this assumption, we compute an aggregate economic freedom score and ordinal ranking of countries, by taking a geometric mean of the five sub-dimensions. For this alternative specification, the marginal impact of each sub-dimension on the aggregate score is no longer independent of the other sub-dimension scores. Consequently, countries with inconsistent levels of economic freedom across sub-dimensions are 'punished' to a greater degree than are countries with less variability across sub-dimensions. Our alternative specification results in considerable movement in terms of country rankings. The geometric mean measure does not appear to explain economic growth as well as the arithmetic mean measure.